(untitled) (Swiss Medical Weekly, 2020)
Polyuria-polydipsia syndrome consists of the three main entities: central or nephrogenic diabetes insipidus and primary polydipsia. Reliable distinction between these diagnoses is essential as treatment differs substantially, with the wrong treatment potentially leading to serious complications. Past diagnostic measures using the classical water deprivation test had several pitfalls and clinicians were often left with uncertainity concerning the diagnosis. With the establishment of copeptin, a stable and reliable surrogate marker for arginine vasopressin, diagnosis of the polyuria-polydipsia syndrome has been newly evaluated. Whereas unstimulated basal copeptin measurement reliably diagnoses nephrogenic diabetes insipidus, two new tests using stimulated copeptin cutoff levels showed a high diagnostic accuracy in differentiating central diabetes insipidus from primary polydipsia. For the hypertonic saline infusion test, osmotic stimulation via the induction of hypernatraemia is used. This makes the test highly reliable and superior to the classical water deprivation test, but also requires close supervision and the availability of rapid sodium measurements to guarantee the safety of the test. Alternatively, arginine infusion can be used to stimulate copeptin release, opening the doors for an even shorter and safer diagnostic test. The test protocols of the two tests are provided and a new copeptin-based diagnostic algorithm is proposed to reliably differentiate between the different entities. Furthermore, the role of copeptin as a predictive marker for the development of diabetes insipidus following surgical procedures in the sellar region is described.